Household Water Consumption, Access, and Affordability in Ledokombo Village: A Mixed-Method Descriptive Study - Mahendra Davin Wicaksono; Adi Mustika; Wahyu Nur Achmadin (Jurnal Inotera, 2026)
Access to clean water remains a fundamental challenge in rural development, particularly in areas characterized by seasonal water fluctuations and fragmented supply systems. This study investigates household water consumption patterns, access structures, and affordability in Ledokombo Village, using a mixed-method descriptive approach. Data were collected from 10 purposively selected households through structured questionnaires, semi-structured interviews, and participant observation to provide both quantitative insights and qualitative depth. The findings reveal that while physical water access is stable, with 100% of respondents reporting 24-hour availability, the community faces a significant economic burden; more than half of the households allocate over 10% of their monthly expenditure to water-related costs. Furthermore, high daily consumption levels often exceeding 300 liters per household reflect demand driven by both domestic needs and broader livelihood activities. The study also identifies that residents actively utilize adaptive coping strategies and water conservation practices in response to resource limitations and financial pressures. The results highlight a structural imbalance between water accessibility and economic affordability, suggesting that rural water governance must transcend infrastructure expansion. It is recommended that policy interventions prioritize tariff optimization, the efficiency of community based systems like PAMSIMAS, and the integration of water quality monitoring to ensure sustainable and equitable water management.